Effect of Macroeconomic Factors on Economic Growth in Indonesia - Mustofa, Hafidz Zainul; Faizin, Moh. (Universitas Airlangga, 2025)
Indonesia’s GDP growth from 2007 to 2022 shows a significant trend, reflecting the positive dynamics of a growing economy. This growth is influenced by macroeconomic factors such as inflation, interest rates, unemployment, fiscal and monetary policies, and international trade conditions. This study investigates the factors affecting Indonesia’s economic growth, mainly focusing on foreign direct investment (FDI), exchange rate, inflation rate, interest rate, and exports. This study uses quantitative methods with quarterly data from 2007 to 2022. The data used are time series data obtained from the Central Statistics Agency (BPS), the Investment Coordinating Board (BKPM), and Bank Indonesia (BI). The analysis used the Vector Error Correction Model (VECM) approach to understand the long-run and short-run relationships. The findings show that FDI is insignificant for Indonesia’s economic growth, while exchange rates and exports negatively impact growth in the short and long run. Inflation has a negative effect in the long run, and interest rates have a positive impact in the long run. Policy implications include improving FDI efficiency, maintaining currency stability, controlling inflation, setting appropriate interest rate policies, and diversifying exports to support economic growth.